Marfan Syndrome in Two Sibs: A Case Report - Chowdhury, Kona; Ahmed, Mesbah Uddin; Uddin, Mohammed Jamal; Roy, Sudipta (Bangladesh Journal of Child Health, 2022)
Marfan syndrome (MFS) is a rare inherited disorder of connective tissue characterized by various phenotypical and genetic manifestations. It involves mutation in FBN1 gene which encodes for microfibrillin glycoprotein fibrillin-1. Predominant involvement occurs in eyes, skeleton and cardiovascular system. Cardiovascular abnormalities such as aortic root dilatation and mitral valve prolapse are the two main life-threatening complications associated with MFS. The diagnosis is based upon clinical findings, some of which are age dependent. If not properly treated, premature death may be caused by the severe cardiovascular and pulmonary complications associated with Marfan syndrome. Therefore, it is important to identify this potentially life-threatening condition in general practice. We are presenting two cases of Marfan syndrome from same family due to its rarity. BANGLADESH J CHILD HEALTH 2021; VOL 45 (2) : 108-110